THE RIGHT WAY TO CATCH A FISH COMES FROM THE LEFT - Loureiro, Luís (2020)
The right aberrant subclavian artery, also known as arteria lusoria, is an anatomical variation described in the literature with an incidence of < 1%. Compression related symptoms can arise from the retroesophageal space and retrotracheal course of the artery. Only a few cases are reported of ischemic symptoms derived from a stenosed or occluded right aberrant subclavian artery. We present a case of ischemic right upper limb symptoms due to an occluded right aberrant subclavian artery treated with a hybrid procedure. The patient was submitted to a left subclavian artery stenting and left to right axillary bypass without complications.